Prevention as a Factor of Economic Sustainability of Workplace Accident Insurance Programs - Abikenova, Sholpan K.; Nasyrova, Gulmira A.; Shayakhmetova, Aizhan G.; Sarybayeva, Inara E. (European Journal of Sustainable Development, 2023)
In the scientific article, the positive impact of preventive accident insurance programs in the workplace is studied. Such programs are the most common and strategically significant type of social security in many countries. Insurance programs often include medical services, vocational rehabilitation, and benefits for injured workers or family members of deceased breadwinners. However, considering current trends, preventive measures aimed at stimulating the improvement of working conditions and occupational safety, active support, and funding of informational and preventive measures remain relevant. The article provides an overview of the use of preventive measures in insurance programs and suggests improving their effectiveness in enhancing working conditions. Firstly, it is proposed to create a unified information database for monitoring insurance contracts, controlling insurance flows on an industry-specific basis, for each enterprise and specific profession, as well as supervising the completeness and quality of preventive measures and the timely provision of compensation to injured workers and rehabilitation measures. Secondly, within the framework of assessing insurance risk, it is suggested to implement comprehensive assessment of occupational risk through the insurance fund. The results of the occupational risk assessment will serve as the basis for applying a two-component insurance tariff, taking into account a surcharge if the working conditions are unsafe. Thirdly, it is proposed to provide occupational health and safety training through insurance financing. Keywords: safe work, risk-oriented approach, insurance, industrial accident, prevention.